Qualidade de vida e a relação com a ocupação profissional: um estudo com militares da reserva e prestadores de tarefa por tempo certo - Rossato, André Tomazetti (2023)
Military activity is a profession that coexists with numerous risk factors, involving physical and psychological capabilities, where through training, field instructions, shooting and activities aimed at war, the military is exposed to the limits of physical and mental exhaustion. , seeking to prepare for the defense of the homeland, in addition to administrative functions that involve meeting deadlines, documentary evidence and all regulatory requirements of the Brazilian Army. However, the Brazilian Constitution ensures good conditions for the military to carry out their functions, compared to the economic reality of the country, being considered an attractive career and much sought after by Brazilians. Some military personnel who went to the reserve may be summoned to return to the Force, exercising technical and/or administrative functions in the Army as a military that keep working in army after retirement (“PTTC”), while the others will remain inactive after active service. This study sought to analyze how the professional occupation interfered in the quality of life of reserve soldiers, in addition to verifying the need to maintain or not a professional occupation after moving to the reserve. The study aimed to compare the degree of quality of life of reserve (inactive) military and PTTC military. The target audience was composed of military men, between 52 and 74 years old, residing in Santa Maria - RS. The research was of the cross-sectional descriptive type, where information was collected on the situation of the aforementioned population from September 2021 to January 2022. To identify the level of quality of life, the WHOQOL-Bref questionnaire was applied. Thus, this study sought to compare the situations of reserve military personnel (inactive and PTCC) to detect the influence of professional occupation on the quality of life of military personnel during the aging process in the work/retirement relation. The data were submitted to descriptive statistics and the quality of life results had their indices classified according to the quality of life levels of each group. Data normality and sphericity were evaluated using the Shapiro-Wilk and Mauchly tests, respectively. Repeated measures ANOVA test was used to compare domains, Bonferroni post-hoc was used to find main effects. For comparisons between groups, an independent t-test was used for parametric variables and the Mann-Whitney U test for non-parametric variables. Statistical analysis was performed with SPSS 20.0 for Windows, with a significance level of α = 0.05 considered in all analyses. There was no significant difference between groups in general quality of life and compared by domains. Both groups were classified as having a good quality of life, according to the WHOQOL classification. Only the environmental domain presented average quality of life in both groups. It was concluded that both inactive soldiers and PTTC have good levels of quality of life and that professional occupation does not significantly interfere in the quality of life of these military.